2015
DOI: 10.1111/geb.12362
|View full text |Cite
|
Sign up to set email alerts
|

Global patterns of mainland and insular pollination networks

Abstract: Aim Interaction networks are being increasingly used to evaluate macroecological patterns. We explored a global dataset to identify differences in the structure of pollination networks from islands (of oceanic and continental origin) and mainlands. For oceanic islands, we further evaluated the effects of key island traits on network structural parameters.Location Fifty-two quantitative plant-pollinator networks from continental islands (n = 23), oceanic islands (n = 18) and mainlands (n = 11) located world-wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
83
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 49 publications
4
83
0
3
Order By: Relevance
“…Nevertheless, our simulation model suggests a high robustness of plants to animal extinction in future communities. This is consistent with the finding that mutualistic networks on islands generally lack a high diversity of animal pollinators and seed dispersers, but apparently maintain their pivotal functions to plants2829. In natural communities, the tolerance of plants to the loss of their mutualistic animal partners is further increased because many plant taxa can locally persist for extended time periods25.…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, our simulation model suggests a high robustness of plants to animal extinction in future communities. This is consistent with the finding that mutualistic networks on islands generally lack a high diversity of animal pollinators and seed dispersers, but apparently maintain their pivotal functions to plants2829. In natural communities, the tolerance of plants to the loss of their mutualistic animal partners is further increased because many plant taxa can locally persist for extended time periods25.…”
Section: Discussionsupporting
confidence: 87%
“…Studies on biotic interactions have often found common network structures within ecological communities, such as nested and modular patterns (Olesen, Bascompte, Dupont, & Jordano, ; Thébault & Fontaine, ). Some of these structures have been confirmed by global studies conducted on mutualistic systems such as plant–pollinators (Traveset et al., ), suggesting that biotic interactions at the community level may be structured following general rules. Our analyses indicate that perennial plant communities in drylands world‐wide present common structures, such as the presence of frequent spatial associations between species and (less commonly) different types of vegetation patches.…”
Section: Discussionmentioning
confidence: 76%
“…B 284: 20162218 richness, among-species competition may nonetheless have promoted high niche partitioning and thus limited the niche width of each species. By contrast, on oceanic islands with low species richness, pollinators presumably expand their floral niches in terms of the number of interaction partners [60][61][62]. This discrepancy may be due to our focus on functional diversity rather than species richness.…”
Section: Discussionmentioning
confidence: 90%